2015
DOI: 10.18267/j.cebr.136
|View full text |Cite
|
Sign up to set email alerts
|

Dark Triad of Croatian Management Students

Abstract: This paper researches the so-called "dark triad" personality traits of management student populations, because of their potential to generate dysfunctional organizational behavior and processes. Namely, the dark triad with characteristics such as lack of empathy, willingness to manipulate others (for self-betterment), antagonism, and belief in one's own superiority can represent a real organizational threat. The goal of this paper is to stimulate thinking and discussion around this issue. The paper is based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Such results can be partially explained by specific personality by management students population where is to find some higher Machiavellianism e.g. on Croatian sample (Bogdanović and Cingula, 2015), and also researchers from Aarhus University (Denmark) found that students of economics and management have personalities with higher drive for social domination and power (index.hr, 03.05.2017. according Independent).…”
Section: Attitude To Whistleblowers Whistleblowing and Potential Whistleblowers' Reactionmentioning
confidence: 97%
“…Such results can be partially explained by specific personality by management students population where is to find some higher Machiavellianism e.g. on Croatian sample (Bogdanović and Cingula, 2015), and also researchers from Aarhus University (Denmark) found that students of economics and management have personalities with higher drive for social domination and power (index.hr, 03.05.2017. according Independent).…”
Section: Attitude To Whistleblowers Whistleblowing and Potential Whistleblowers' Reactionmentioning
confidence: 97%
“…The analysis involving a comparison of both instruments (DD-SD3) highlighted the greater convergence and incremental validity of the SD3 in terms of longer and more established measures of the dark triad traits, adequate discriminant validity, and criterion validity concerning the traits of the five-factor model [ 19 ]. Due to these superior psychometric properties, the SD3 has been widely propagated worldwide [ 3 , 20 , 21 ], including adaptations and their analyses in countries as diverse as Germany [ 22 ], Argentina [ 23 ], China [ 24 ], Poland [ 25 ], Croatia [ 26 ], Russia [ 27 ], Iran [ 28 ], Japan [ 29 ], Taiwan [ 30 ], Holland [ 31 ], Serbia [ 32 ], Thailand [ 33 ], France [ 34 ], Turkey [ 35 ], and Spain [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior work also compares Croatia with others. An interesting paper, in our view, compares business students in Croatia with those in Canada on three psychological characteristics, Machiavellianism, Narcissism, and Psychopathy labeled the “Dark Triad.” Implied is the belief these would be dysfunctional should they migrate to the business community, and this is potentially a larger problem given that Croatian respondents scored higher than the Canadians (Bogdanovic & Cingula, 2015). A 2015 paper compares the ethical influence of gender, nationality, and citizenship on one's moral philosophy and ethical behavior in several Central and East European Countries including Croatia.…”
Section: Introductionmentioning
confidence: 99%